Take-up of Free School Meals: Price effects and peer effects - Angus Holford (University of Essex, Institute for Social and Economic Research (ISER), 2012)
Almost 300,000 entitled children do not participate in the UK's Free School Meals (FSM) programme, worth up to 400 per year. Welfare take-up can be stigma and lack of information. This paper uses a school-level dataset and fixed-effect instrumental variables strategy to show that peer-group participation has a substantial role in overcoming these barriers. Identification of endogenous peer effects is achieved by exploiting a scheme which extended FSM entitlement to all children in some school cohorts. Results show that in a typical school a 10 percentage point rise in peer-group take-up would reduce non-participation by almost a quarter.
Keywords: H75; I28; I38; Z13; 330; school meals; peer effects; welfare stigma; aggregated data